EL INDIVIDUO Y LA NACIÓN. EL SUJETO Y LO ABSOLUTO EN LAS FILOSOFÍAS DEL LENGUAJE DE HUMBOLDT Y FICHTE - Navarro Pérez, Jorge (Daimon Revista Internacional de Filosofia, 1994)
This paper sketches an analysis of W. v. Humboldt's reaction to Fichte's philosophy of language in the essay «On the Speech Faculty and the Origin of Language» and in the «Discourses to the German Nation» (1808). By using the idea of the individual, it tries to provide an alternative to the interpretations of Humboldt's writings that underline the idea of the absolute.